Make it STING: nanotechnological approaches for activating cGAS/STING as an immunomodulatory node in osteosarcoma - O’Donoghue, Jordan C.; Freeman, Fiona E. (Frontiers in Immunology, 2024)
Osteosarcoma is a highly aggressive bone cancer primarily affecting children, adolescents, and young adults. The current gold standard for treatment of osteosarcoma patients consists of two to three rounds of chemotherapy, followed by extensive surgical intervention from total limb reconstruction to amputation, followed by additional rounds of chemotherapy. Although chemotherapy has advanced the treatment of osteosarcoma significantly, the overall 5-year survival rate in resistant forms of osteosarcoma is still below 20%. The interaction between cancer and the immune system has long been recognized as a critical aspect of tumour growth.Tumour cells within the tumour microenvironment (TME) suppress antitumour immunity, and immunosuppressive cells and cytokines provide the extrinsic factors of tumour drug resistance.Emerging research demonstrates an immunostimulatory role for the cGAS/STING pathway in osteosarcoma, typically considered an immune-cold or immunosuppressed cancer type. cGAS/STING signalling appears to drive an innate immune response against tumours and potentiates the efficacy of other common therapies including chemo and radiotherapy. Nanotechnological delivery systems for improved therapy delivery for osteosarcoma have also been under investigation in recent years. This review provides an overview of cGAS/STING signalling, its divergent roles in the context of cancer, and collates current research which activates cGAS/STING as an adjuvant immunomodulatory target for the treatment of osteosarcoma. It will also discuss current nanotechnological delivery approaches that have been developed to stimulate cGAS/STING. Finally, it will highlight the future directions that we believe will be central to the development of this transformative field.